PENDIDIKAN DINIYAH DI ERA GLOBALISASI - Hasbi Indra (Institut Agama Islam Ngawi, 2019)
AbstractDiniyah Education in Society or in Islamic Boarding Schools (pesantren)one of a pillar urgent for the National Education Systems. The diniyah education a part of national system of education that a measurement quality of national of education. This time national education including its diniyah education are face thechallengspositive effects or negative effects. The reseach of purposes how to know the development of its and how the affects of the nation ini competation era. The cahallengs are holds face, therefore, this educations shoulds be readiness alumni have deep-knowledge, skillsÂ and the institution shoulds to manage with professional management. The aimsof this study is to understand how the diniyah education prepare these students to face the globalization of challenges. It is conducted qualitatively using the data derived from the relevant literatures.Â Key words: diniyah education, challenges, globalizationÂ